Effect of alternate wetting and drying versus continuous flooding on carbon rates in rice and soil (International Journal of Agricultural Research, Innovation and Technology, 2016)
An experiment was conducted at Bangladesh Institute of Nuclear Agriculture (BINA) farm, Mymensingh, Bangladesh during 2010-2011 to find out the effect of different water and organic residue rates on rice and soil. Organic carbon rates from cow dung (0.5, 1.0, 1.5 and 2.0 t C ha-1 including control) were evaluated under alternate wetting and drying (AWD) and continuous flooding (CF). CF system in combination with chemical fertilizers and 2.0 t C ha-1 produced the maximum plant height, filled grains tiller-1, 1000 grains weight, grain and straw yields. Combined use of 2.0 t C ha-1 cow dung and CF system decreased CO2-C gas emission, increased carbon accumulation in above ground biomass of rice as well as carbon sequestration in soil. This treatment also helped to optimize soil pH. Based on these results, it may be concluded that continuous flooding system in combination 2.0 t C ha-1 increased grain yield, carbon accumulation in above ground biomass, carbon sequestration in soil and optimized soil pH.Int. J. Agril. Res. Innov. & Tech. 6 (1): 26-33, June, 2016